Estudo comparativo dos modelos da onda cinemática e da onda difusiva na análise de propagação de cheias, em função dos parâmetros hidráulicos da bacia - Gomes, Vanessa Ueta (2006)
Models of Kinematic Wave and diffusive wave were applied in a natural river, to study the propagation of a flood wave in the water body. These models are derivations of the Dynamic Wave Model, from simplifications in the Saint Venant equations, where some terms are neglected. In the solution process of differential equations relevant to the model, we used the method of finite differences, wherein the explicit scheme approach was applied to the kinematic wave, while the implied approximation scheme was applied to the diffusive wave. For this research, a computer program in FORTRAN language was developed and allowed road simulations were performed for different scenarios found in natural rivers. Studies to verify the sensitivity of the models with respect to the hydraulic parameters of the basin, were performed. the influence of linearization of differential equations, which make up the models, we calculations of the control variables also was verified. The results showed that the model of the kinematic wave is most sensitive to the coefficient of roughness of the channel walls, while the model of the diffusive wave is more sensitive to the channel bottom slope parameters, where this parameter acts directly on the damping process wave propagation. The results also showed that for the scenarios used in the simulations, the linearization process of differential equations does not affect considerably the solution models.